Impact of Demographic Traits and Personality Traits of Investors on Their Risk-Bearing Capacity: A Study with Special Reference to Investors of Kerala - K, Athira; Kakkakunnan, Mohamed Kutty (Indian Journal of Finance and Banking, 2020)
Investment decisions form a major part of every individual’s life. Behavioral finance which puts forward a new dimension in the field of finance recognizes that investment decisions are made after considering numerous psychological, economical and social factors. One of the important criteria considered while making any such decision is the risk. It includes uncertainties associated with the investment opportunity as well as the investors’ risk-bearing capacity. Investors’ risk-bearing capacity is in turn determined by numerous other aspects. An effort is made here to determine whether the risk-bearing capacities of investors are influenced by the demographic factors and personality traits. 120 investors of Kerala State were selected as the sample for this purpose. Analytical results indicated that the risk-bearing capacity is dependent on gender, occupation, and monthly income of the investors. Further, it was noticed that those who have low neuroticism scores and high scores in agreeableness, extraversion, and conscientiousness took higher risks compared to others. This indicated that neuroticism trait was found to have a negative correlation with risk-bearing capacity whereas; agreeableness, extraversion, and conscientiousness were found to have a positive relation. The study concluded that factors like demography and personality have a strong influence on an investor’s risk-bearing capacity.